Three-dimensional structural location and molecular functional effects of missense SNPs in the T cell receptor Vbeta domain - Wang, Zhen; Moult, John (Proteins, structure, function, and bioinformatics, 2003)
The mechanisms by which human single nucleotide polymorphisms (SNPs) influence susceptibility to disease are not yet well understood. In a previous study, we developed a structure-based model that may be used to identify which missense SNPs are neutral and which are deleterious to protein function and so potentially involved in disease (Wang and Moult, Hum Mutat 2001;263-270). The model has now been applied to a set of 54 missense cSNPs in the 46 functional T-cell receptor Vbeta-genes. Most of these missense cSNPs are found to be neutral, but 10 are identified as likely deleterious to protein function. Only one was previously associated with disease. We suggest that the others may be disease related but that redundancy in the T-cell response prevents any simple, monogenic effect. Therefore, these SNPs are the most likely contributors to complex, polygenic disease traits. It has been noted that there is a surprisingly high (74%) fraction of nonsynonymous SNPs in these genes. Contrary to expectation, the analysis shows that these are not associated with an unusually high fraction of deleterious SNPs, nor do they significantly contribute to a larger range of antigen recognition or a reduced superantigen-binding repertoire.